The relationship of junior high school students' self-concept to certain variables - Sanchez, Zenaida B.
An understanding of the student's self-concept will help educators gain the proper perspective and insights into the student's needs and problems. This study attempted to determine the levels of self-concept of 497 junior students of the Davao City High School and find out the relationship between self-concept and four different variables: sex, mental ability, socio-economic status and academic achievement. The main instrument used was Pasao's self-concept Rating Scale. Conclusions drawn from the study were that majority of the juniors have low self-concept while the lesser minority have high self-concept. There were no significant relationships between self-concept and sex and socio-economic status. However, there were significant relationships between self-concept and mental ability and achievement.